2001
DOI: 10.1055/s-2001-19364
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Development of the Axillary Complex and Extrafloral Nectaries in Capparis retusa Griseb.

Abstract: The structure, organization and development of the axillary complex and extrafloral nectary in Capparis retusa Griseb. was analysed for the first time. The axillary complex presents three uniserial descending buds. Subordinated shoots originate from the distal and middle bud, while the proximal bud is usually quiescent. Close to the top of the axillary complex there is a subglobulous and umbilicated extrafloral nectary, normally visited by nectivore ants; a chronological coincidence between secretion, producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The vascular tissue can be composed of both phloem and xylem, e.g., in Capparis retusa/Capparidaceae (Di Sapio et al, 2001), or have only phloem, as seen in Arabidopsis (Baum et al, 2001) and B. napus (Davis et al, 1986). In other families, nectary vascularization is missing completely (e.g., Swietenia/Meliaceae, petaline nectaries: Paiva, 2011; Boswellia/Burseraceae, nectariferous ring: Giuliani et al, 2012).…”
Section: Nectary Structurementioning
confidence: 96%
“…The vascular tissue can be composed of both phloem and xylem, e.g., in Capparis retusa/Capparidaceae (Di Sapio et al, 2001), or have only phloem, as seen in Arabidopsis (Baum et al, 2001) and B. napus (Davis et al, 1986). In other families, nectary vascularization is missing completely (e.g., Swietenia/Meliaceae, petaline nectaries: Paiva, 2011; Boswellia/Burseraceae, nectariferous ring: Giuliani et al, 2012).…”
Section: Nectary Structurementioning
confidence: 96%
“…Phloem and xylem are present in Capparis retusa (Brassicaceae; Di Sapio et al, 2001), Ecballium elaterium (Cucurbitaceae; Fahn & Shimony, 2001), Solanum stramonifolium (Solanaceae; Falcão et al, 2003), and Hexisea imbricata (Orchidaceae; Stpiczyńska et al, 2005a) (see also the examples reported by Fahn (2000) and Nepi (2007)). …”
Section: Pacini and Nepimentioning
confidence: 97%
“…The closest relative of Brassicaceae that possess extrafloral nectaries is Capparis retusa (order Brassicales, family Capparaceae), where the nectaries look like umbilicated glands containing a specialized parenchyma vascularized with xylem and phloem (Di Sapio, Gattuso & Prado 2001). Moreover, floral nectaries in many species of Brassicaceae have been described as protuberant gland structures surrounded by modified stomata, which maintain a firm contact between cells and subjacent parenchyma cells (Davis, Peterson & Shuel 1986; Davis et al .…”
Section: Discussionmentioning
confidence: 99%